The role of metformin in tuberculosis control among TB and diabetes mellitus comorbid individuals - Tetteh, Phillip; Danso, Emelia K.; Osei-Wusu, Stephen; Yeboah-Manu, Dorothy; Asare, Prince (Frontiers in Microbiology, 2025)
Tuberculosis (TB) is a major global health concern, and its control is particularly hindered in patients with comorbidities such as type 2 diabetes mellitus (TBDM). Metformin, a commonly prescribed antidiabetic medication, has gained attention because of its potential role in improving TB treatment outcomes in patients with TBDM. This review aims to assess the role of metformin in TB case management among TBDM comorbid individuals. By reviewing the available literature, we aimed to explore the potential benefits, complications, mechanisms, and considerations surrounding metformin use as an adjunctive therapy for TB treatment. The findings of this review will shed light on current understanding and highlight areas for further investigation.